A systematic review on the Roles and Responsibilities of Sport Manager’s Professional Competency - Daniel Getnet Admit (Journal Research of Social Science, Economics, and Management, 2023)
Management is one of the most important human activities and has a critical impact on the life, growth, development, or destruction of organizations. The skills necessary for management vary at different levels, and their distinction necessitates the identification of roles and responsibilities that managers use to play. Even skills vary according to the level of management. This systematic review aims to synthesize the roles, responsibilities, and skills of sport managers. This is an attempt to use PRISMA meta-synthesis. By using keywords like "sport managers," "managers' role and responsibility," "manager competency," and "manager efficacy," 96 articles were duplicated from Elsevier, PERMED, and Google Scholar databases. Six articles that fit the inclusion criteria were incorporated into this paper. A holistic perspective on competency-based measurement drawn from organizational theory and role theory was used as a discussion point. Although the sports industry has distinct characteristics, the roles of sports managers are to create and organize schedules, promote clients through various forms of media, endorsement deals, negotiate contracts, maintain positive public relations, ensure compliance with rules and policies, etc. To perform these tasks requires human, technical, and conceptual skills to plan, organize, lead, and control the activities. Finally, the reviewers recommended that the managers acquire and know the management skills necessary for the success of their club.